A Proposed Design Method for Sparse Array Antenna by Using the Spacing Coefficient Algorithm. (14th September 2022) - Sandi, Efri; Diamah, Aodah; Yuliatmojo, Pitoyo; Maruddani, Baso
Abstract : One of the major challenges in developing various practical communication systems is reducing device complexity and development costs. In this study, a linear sparse array antenna design problem is addressed and a new approach for density taper element spacing by using the spacing coefficient algorithm is proposed. This method is a mathematical approach to obtain the distance between array elements by developing a spacing coefficient d n   for each element to achieve radiation performances with a minimum number of antenna elements. The simulation and measurement results show a significant improvement in array performance compared to other sparse array design methods, such as the CDS sparse array method in our previous work.